Contingent effect of board gender diversity on performance in emerging markets: Evidence from the Egyptian revolution - Melsa Ararat; Moataz El-Helaly; Alan Lowe; Nermeen Shehata (Journal of Risk and Financial Management, 2021)
The 2011 Egyptian revolution was associated with significant political and social upheaval, followed by societal changes and attempts by policymakers to reduce the marginalisation of women and promote their inclusion in the economy. Drawing on this background, the authors compare the effect of board gender diversity before and after the revolution. Results indicate that gender diversity in corporate boards is coupled with improvements in firm performance in the immediate post revolution phase. This evidence provides insights into the contextual factors related to diversity and performance relationship and supporting arguments for regulatory changes to further encourage women's representation on boards.
Keywords: 330; corporate governance; boards of directors; Egypt; gender diversity; Egyptian Revolution